Kajian Komposisi Jalur Hijau Jalan di Kota Yogyakarta Terhadap Penjerapan Polutan Timbal (Pb) - Fadlhinsyah Damanik (Universitas Muhammadiyah Yogyakarta, 2014)
This research aims to examine the composition of the green belt and its ability to adsorb particles of lead (Pb), determine the amount of particulate emissions of lead in the ambient air resulting from vehicle traffic activities and evaluate the composition of green belt some streets. The research was conducted using a survey method, the technical implementation is done by observation, questionnaires and secondary data collection. Sampling was done by purposive sampling is the selection of the sample with certain considerations deemed relevant according to the research objectives. Data were analyzed descriptively. The result showed that the green belt in three streets was dominated by Angsana trees (Pterocarpus indicus) form a line 1 (one) row crops. The composition of the green belt type, quantity, function, size, and distribution of plants available have not been able to reduce the concentration of lead (Pb) and thus require rearrangement. The roads planted with tree of Angsana (Pterocarpus indicus) and Tanjung (Mimusops elengi) had concentrations of lead (Pb) lower, as much as 1,39 µg/m3 at Urip Sumoharjo and as much as 1,11 µg/m3 at Laksda Adisucipto compared the road that only planted tree of Angsana (Pterocarpus indicus) is contained at Ahmad Dahlan with (Pb) concentration as much as 1,56 µg/m3. Concentrations of lead (Pb) in the third road was approaching the threshold value, but still below the quality standards specified.